New onset depression and anxiety in patients with an implantable cardioverter defibrillator during 24 months of follow-up. (24th May 2021) - Pedersen, SS; Nielsen, JC; Wehberg, S; Jorgensen, OD; Riahi, S; Haarbo, J; Philbert, BT; Johansen, JB
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Danish Heart Foundation OnBehalf: DEFIB-WOMEN study group Background: Patients adjust well to living with an implantable cardioverter defibrillator (ICD), but 20% develop anxiety and depression that may compromise their quality of life (QoL) and increase risk of ventricular tachyarrhythmias and mortality. Purpose: We examined the incidence and correlates of new onset anxiety and depression during 24 months of follow-up in ICD patients without depression and anxiety. Methods: Patients with a first-time ICD (n = 1040) enrolled in the national, multi-centre prospective observational DEFIB-WOMEN study completed questionnaires on anxiety, depression and physical QoL at baseline, 3-, 6-, 12-, and 24 months. Information on demographic and clinical data was obtained from the Danish Pacemaker and ICD Register. Results: During 24 months of follow-up, 46-57 (4%-5%) patients developed new onset anxiety and 42-47 (4%-5%) new onset depression. The incidence of new onset comorbid anxiety and depression was higher with 69-80 (7%-8%). Age [HR:0.54; 95%CI:0.36-0.80], marital status [HR:1.66; 95%CI:1.01-2.73], secondary prevention indication [HR:1.43; 95%CI:1.00-2.04], Type D personality [HR:2.50; 95%CI:1.62-3.86], and lower self-reported physical functioning [HR:1.48; 95%CI:1.00-2.17] were associated with new onset anxiety during follow-up. Age [HR:0.57; 95%CI:0.37-0.89], higher self-reported physical functioning [HR:0.46; 95%CI:0.25-0.85], smoking [HR:2.13; 95%CI:1.33-3.40], Type D personality [HR:2.53; 95%CI: 1.57-4.05], and lower self-reported physical functioning [HR:1.64; 95%CI:1.08-2.48] were associated with new onset depression. Conclusion: Between 4%-8% of patients with a first-time ICD with no anxiety or depression at baseline are at risk of new onset anxiety, depression, or comorbid anxiety and depression up to 24 months post implant, suggesting that safeguarding their QoL and prognosis warrants that we screen patients not only at baseline.